Immunogenicity of an Inactivated Canine Adenovirus Type 1 Vaccine for Foxes - Fu, Yang; Sun, Jie; Lian, Shizhen; Deng, Xiaoyu; Zhang, Lei; Shao, Jikai; Yu, Hongguang; Yan, Xijun; Zhu, Yanzhu (Frontiers in Veterinary Science, 2022)
Canine Adenovirus type 1 (CAdV-1) is the etiologic agent of fox encephalitis. As with most viral agents, the best method of prevention is vaccination. In this study, the CAdV-1 strain F1301 strain to construct a new type 1 canine adenovirus inactivated vaccine candidate to evaluate its safety and immunogenicity in silver foxes. Next, animals were challenged and survival rates of animals vaccinated with either the commercially available or the current candidate vaccine were examined. The results confirmed that the inactivated CAdV-1 vaccine prepared in this study can effectively protect against challenge with virulent CAdV-1 in silver foxes, and the safety profile was improved relative to that of the commercial vaccine. This study confirmed that the fox CAdV-1 F1301 strain can be used as a platform for an inactivated CAdV-1 vaccine.